Kajian Kinerja Pengelolaan KPHL Kota Ambon, Provinsi Maluku - Parera, Evelin; Purwanto, Ris Hadi; Permadi, Dwiko Budi; Sumardi, Sumardi (MAKILA, 2020)
Since the establishment of the KPHL Kota Ambon in 2010 until nearly a decade, how has the development been managed? How management performance. Therefore, through this study, the performance of the management of the KPHL Kota Ambon aims to determine the management performance of KPHL Kota Ambon. This research was conducted at the KPHL Kota Ambon, November-December 2019. The research was conducted using Criteria and indicators made by Forest Wach Indonesia ((FWI), 2014), document verification, and in-depth interviews with the Head of the UPTD. Pulau Ambon dan Pulau-Pulau Lease. Quantitative analysis method based on calculation procedures made by FWI, 2014. The index results are then described using descriptive methods. The results of the study concluded that 1) The performance of the management of the KPHL Kota Ambon was in the medium criteria index; 2) Management of KPHL Kota Ambon is not yet optimal because the RPHJP has not been ratified as a basis for the preparation of the RPHJPd and Business Plan; 3) The organizational structure has not been filled and the available human resources are not yet competent in the management of FMUs because they have not attended special education and training on FMU management; 4) KPHL Kota Ambon management activities is still limited to socialization activities that have not been routinely so that not many people know about KPHL Kota Ambon